Sistem Penunjang Keputusan Pemilihan Karyawan Terbaik Dengan AHP Pada PT. LSP Gatensi Karya Konstruksi - Melan Susanti; Rahmawati Rahmawati; Lidya Caroline Terah; Nova Mardiani Nurdin; Ali Haidir (Bianglala Informatika, 2026)
The rapid development of information technology today has significantly impacted various sectors, including decision-making in the workplace. PT. LSP Gatensi Karya Konstruksi requires a system capable of supporting the employee evaluation process in an objective and fair manner to determine the best employee. The assessments carried out so far have not been objective, so this research is needed. The evaluation is based on several criteria, namely attendance, teamwork, performance, and work ethics. The purpose of this research is to design a decision support system that facilitates and accelerates the process of selecting the best employee. The method used in this research is the Analytical Hierarchy Process (AHP), which allows for structured and systematic comparisons between criteria to generate accurate priority weights. The results of this study indicate that the application of the AHP method in the decision support system can assist management in determining the best employee objectively, transparently, and efficiently. Therefore, this system is expected to improve employee motivation and performance within PT. LSP Gatensi Karya Konstruksi.